PENERIMAAN DIRI PADA ISTRI YANG MEMILIKI SUAMI HOMOSEKSUAL - IRMA ROSALINDA LUBIS; ANANDA RASULLIA (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2014)
This research was conducted to find the stages of self-acceptance in wife with homosexual husband. The stages of self-acceptance taken from Christopher Germer’s stages of self-acceptance and consists of five stages; aversion, curiosity, tolerance, allowing, and friendship. This research also wanted to find out the reason underlying why a wife still keeping her marriage alive with homosexual husband.This research was conducted using qualitative methods because the phenomenon to be studied belong to a unique phenomenon. This research uses purposive sampling technique to selected its subject. The approach used in this research is case study. Study results showed that both of the subjects are already achieved three out of five stages of self-acceptance. The reason why they still keeping up their marriage alive are because of affection towards the husband, religion factor, and family factor